The Physical Education Learning Management Context and the Physical Literacy Guideline on Basketball Subject for Upper Secondary School, Bangkok Metropolitan - Mahakanok, Jaturon; Srisiri, Sununta; Chimwong, Luxsamee (Ratchaphruek Journal, 2024)
This study aimed to examine the physical education learning management context and physical literacy guideline on basketball subject in upper secondary school, Bangkok Metropolitan. The research methodology employed a qualitative approach, focusing on two key informant groups: Twenty physical education teachers were selected from the sample size calculation using the G*Power software; and A group of ten experts were selected using the purposive method. In-depth interviews with 2 groups using a semi-structured interview. The qualitative data analysis included content analysis and inductive analysis. The results showed the following context of physical education learning management: 1) The teachers emphasized group and games activities, collaborative learning and demonstration-based; 2) The content sequencing ranged from easy to challenging skills, with an emphasis on engaging and challenging activities; and 3) The teachers perceived differences in student attitudes between individualized assessment (with higher pressure) and group assessment. The study also suggested the following guidelines for promoting physical literacy. The most crucial components for upper secondary school students are mental and physical aspects. The activities should be collaborative, challenging, enjoyable, and positively reinforcing, and the assessment of mental and social components should be paired with observation.